A mathematical orchard : problems and solutions - Krusemeyer, Mark; Gilbert, George T. , 1957-; Larson, Loren C. , 1937- (MAA problem books series, 2012)
This volume is a republication and expansion of the much-loved Wohascum County Problem Book, published in 1993. The original 130 problems have been retained and supplemented by an additional 78 problems.